The New era of carbon accounting : issues and implications for Latin American and Caribbean exports - LaFleur, Marcelo (UN ECLAC SantiagoCL, 2011)
Focuses on the recent trends of private and unilateral efforts to account for the carbon emissions of traded goods, with the objective of identifying possible risks and opportunities for Latin American and Caribbean exporters.